Highway wind power energy assessment of Al-Durra highway street in Baghdad, Iraq - Adnan Ahmed Abdul Raheem; Wadhah Esmaeel Ibraheem (Institute of Advanced Engineering and Science, 2020)
In certain spots on the planet which have less attainable of utilizing enormous breeze power plants, the expressway wind vitality can be utilized to help little loads in the main grids. Interstates road lighting for instance of that heaps that is expending a great deal of vitality and cost every year. When the vitality that originates from vehicles development along the highway avenues can be taken in thought, this paper has examined the outcomes if moment vehicles wind speed during 24 hours per day. 24 hours, brief interim of vehicles wind speeds have been estimated by utilizing anemometer put in the road. A vertical pivot wind turbine (VAWT) has been proposed to be utilized in this task. All venture regulation has been simulated by utilizing Opendss program; it can support time series simulation. The outcomes demonstrated that the undertaking is possible to be utilized in Al-Durra Highway Street. The normal breeze speed of moving vehicles is 4.7 m/s which can deliver 67.3 watt by the proposed turbine. The got energy saw that it as contributed to be utilized by the maingrid during the day time. All the demonstrated bends of the outcomes speak to the Iraq grid support by diminishing the main demand and operational expenses too.